التغير والاستقرار في سلوك الاسهم العادية خلال الفواصل الزمنية "دراسة تطبيقية لعينة من المصارف في بورصة عمان" - النعيمي شهاب الدين حمد (Journal of Economics and Administrative Sciences, 2008)
Knowing the conduct of the common stocks during the different intervals of time (quarterly and yearly) is an important step in choosing and administrating the portfolio of common stocks which be in accordance with the tendency of the investor toward risk and revenues. This is an attempt to understand the behavior of this common stocks in Amman stock Exchange to discover the extent of change in its behavior for employing them by the managers in identifying the accurate and beneficed investments , which meet the ambitions of Arab investor.